KESEPIAN SEBAGAI FAKTOR RISIKO KECEMASAN REMAJA PADA SISWA SMA - Nugrahati Carsita, Wenny; Wahyu Kusumawati, Mira; Ichsan Basir, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2026)
Background: Loneliness is one of the psychosocial problems often experienced by adolescents and is significantly associated with mental health. Loneliness also closely related to the levels of anxiety reported among high school students. Purpose: This study aims to analyze the relationship between loneliness and anxiety among adolescents in senior high school Methods: This study was designed using an analytical method through a cross-sectional approach. The research sample involved 89 high school students selected using purposive sampling. The UCLA Loneliness Scale questionnaire was used to measure loneliness, while anxiety was measured using the Mini Mindhear Youth Scale V.1 (MMYS V1). Testing the relationship between variables was conducted through Pearson Chi-square analysis Result: A significant relationship was found between loneliness and anxiety in adolescents (p = 0.040). Teenagers with high levels of loneliness experience more mild to severe anxiety Implication: Schools and health workers are expected to conduct early detection and develop social support-based interventions, such as peer counseling or peer-support groups, to reduce loneliness and anxiety among adolescents. These programs are relevant for implementation in secondary school settings because adolescents tend to be more open and comfortable sharing emotional problems with their peers Keywords: adolescents; anxiety; loneliness